Treatment of engineering waste slurries by microbially induced struvite precipitation mechanisms - He, Yuhan; Liu, Shiyu; Shen, Gangqiang; Pan, Muzhi; Cai, Yanyan; Yu, Jin (Frontiers in Bioengineering and Biotechnology, 2023)
With societal development, the growing scale of engineering construction, and the increase in environmental protection requirements, the necessity of engineering waste mud disposal is becoming increasingly prominent. In this study, microbially induced struvite precipitation (MISP) was introduced to treat engineering waste mud. The study mainly focused on: i) the optimal mineralization scheme for microbially induced struvite precipitation, ii) the feasibility of the process and the effect of reaction parameters on treating engineering waste mud with microbially induced struvite precipitation, and iii) the mechanism of microbially induced struvite precipitation in treating engineering waste mud. The results showed that the waste mud could be well treated with 8.36×106 cell⋅mL−1 bacteria, 10 mM urea, 20 mM phosphate buffer, and 25 mM MgCl2 at pH 7. The kaolin suspension could be effectively flocculated. The flocculation rate reached approximately 87.2% under the optimum mineralization conditions. The flocculation effect was mainly affected by the concentrations of reactants and heavy metals and the suspension pH. The X-ray diffraction (XRD) patterns showed a strong struvite (MAP) diffraction peak. Scanning electron microscopy (SEM) images indicated that under the optimal mineralization conditions, the crystals were large and showed prismatic shapes tilted at both ends with adhered kaolin particles. In summary, this manuscript provides an effective way to treat engineering waste mud, and the findings should have a positive effect on enhancing soil fertility and preventing secondary pollution.